2014
DOI: 10.3389/fmicb.2014.00635
|View full text |Cite
|
Sign up to set email alerts
|

Sodium houttuyfonate affects production of N-acyl homoserine lactone and quorum sensing-regulated genes expression in Pseudomonas aeruginosa

Abstract: Quorum sensing (QS) is a means of cell-to-cell communication that uses diffusible signaling molecules that are sensed by the population to determine population density, thus allowing co-ordinate gene regulation in response to population density. In Pseudomonas aeruginosa, production of the QS signaling molecule, N-acyl homoserine lactone (AHL), co-ordinates expression of key factors of pathogenesis, including biofilm formation and toxin secretion. It is predicted that the inhibition of AHL sensing would provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Some compounds extracted from plants possess antibacterial activity with higher or overlapping MIC values and anti-QS and anti-biofilm activities even at lower concentrations [44,45]. Based on susceptibility testing, baicalin lacks anti- P .…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds extracted from plants possess antibacterial activity with higher or overlapping MIC values and anti-QS and anti-biofilm activities even at lower concentrations [44,45]. Based on susceptibility testing, baicalin lacks anti- P .…”
Section: Discussionmentioning
confidence: 99%
“…Alfaro et al (2004) synthesized two substrate analogs of intermediates of the initial and final steps in AI-2 synthesis and observed that these compounds could inhibit such synthesis. Recently, sodium houttuyfonate (commonly used in traditional Chinese medicine for infectious diseases) was shown to decrease AHL production and the associated virulence in P. aeruginosa (Wu et al 2014), although the mechanism in this case was a decrease in the expression of lasI (a luxI homolog) rather than its acting as a substrate analog. In addition to the biosynthesis of AI-2 through the luxS gene, A. hydrophila has an AHL-based QS system in which ahyI and ahyR act as luxI and luxR homologs (Cao et al 2012).…”
Section: Quorum-sensing Inhibitors Used In Aquaculturementioning
confidence: 98%
“…Staphylococcus epidermidis strain ATCC 35984, which was obtained from the National Institute for the Control of Pharmaceutical and Biological Products (NICPBP, Beijing, China), was normally cultured in tryptone soy broth (TSB) (Aoboxing Bio-tech, Beijing, China) and grown in a shaker under normal condition (37ºC, 5.4 g) unless otherwise mentioned. Minimum inhibitory concentrations (MIC) of SH and erythromycin against S. epidermidis were determined by CLSI standard method according to our previous research (24,25).…”
Section: Bacterial Strains and Culturesmentioning
confidence: 99%
“…Previously, our group found that SH is promising and effective at repressing pathogenic related biofilm formation and motility of Pseudomonas aeruginosa (20)(21)(22), and can inhibit S. epidermidis and Candida albicans (20,23), and act synergistically with Na 2 -EDTA and levofloxacin against biofilm formation of P. aeruginosa, S. aureus and C. albicans (23,24). In addition, we found that SH is a possible natural analog of N-acyl-homoserine lactone, and can effectively inhibit the Las quorum sensing (QS) system and regulated virulence factors of P. aeruginosa (25). However, owing to the high resistance of antimicrobial agents of biofilm, we found that SH alone cannot effectively inhibit the biofilm formation of S. epidermidis.…”
Section: Introductionmentioning
confidence: 99%